Synthesis and Characterization of Transition Metal(II) Complexes Derived from (E)-N-(4-Methylbenzylidene)-2-((Z)-(4-Methylbenzylidene) Amino)Benzamides: Investigation of Biological Activities - Bhovi, Venkatesh K (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
We synthesized a novel series of transition metal(II) complexes 5a-h by reacting key transition metals (Co, Cu, Zn, Ni) with the Schiff base 3, derived from (E)-N-(4-methylbenzylidene)-2-((Z)-(4-methylbenzylidene)amino)benzamide. Schiff base 3 was previously prepared by reacting 2-aminobenzohydrazide 1 with 4-methylbenzaldehyde 2. The structures of the metal complexes were characterized using IR, NMR, mass spectrometry, and elemental analysis. We evaluated the synthesized metal complexes for antioxidant, antimicrobial, and antifungal activities. Notably, compounds 5e and 5c exhibited enhanced antimicrobial activity compared to the free ligand. Compounds 5g and 5a showed significant activity against various bacterial strains. Additionally, the hydrated metal complexes 5b, 5d, 5f, and 5h demonstrated moderate to good antimicrobial activity. In terms of antioxidant activity, most of the metal complexes displayed moderate to good activity comparable to ascorbic acid. Our bioassay results highlighted compounds 5e and 5c as effective antimicrobial agents against highly resistant microbial strains.